Protective effects of anti-oxidant supplementations on contrast-induced nephropathy after coronary angiography: an updated and comprehensive meta-analysis and systematic review - Ali-Hasan-Al-Saegh, Sadeq; Sedaghat-Hamedani, Farbod; Kayvanpour, Elham (Kardiologia polska, 2016)
BACKGROUND AND AIM: This systematic review with meta-analysis sought to determine the strength of evidence for effects of antioxidants (AO) such as N-acetyl cysteine (NAC), vitamin C, vitamin E, and alpha-lipoic acid on the incidence of contrast-in-duced nephropathy (CIN), requirement for haemodialysis, level of serum creatinine, and mortality after coronary angiography. METHODS AND RESULTS: After Medline, Embase, Elsevier, Sciences online database, and Google Scholar literature searches, studies with randomised controlled design were selected for the meta-analysis. The effect sizes measured were odds ratio (OR) for categorical variables and standard mean difference (SMD) with 95% confidence interval (CI) for calculating differences between mean changes of serum creatinine in intervention and control groups. A value of p < 0.1 for Q test or I2 > 50% indicated significant heterogeneity between the studies. Literature search of all major databases retrieved 2350 studies. After screening, a total of 49 trials were identified that reported outcomes. Pooled treatment effect analysis revealed that NAC (OR of 0.79; 95% CI 0.69-0.9; p = 0.000), vitamin C (0.63; 95% CI 0.45-0.89; p = 0.000), and vitamin E (OR of 0.5; 95% CI 0.27-0.92; p = 0.026) could significantly reduce the incidence of CIN. NAC (SMD of -0.119; 95% CI -0.191 - 0.046; p = 0.000), but not vitamin C (SMD of -0.08; 95% CI -0.22-0.04; p = 0.1) and vitamin E (-0.25; 95% CI -0.46-0.05; p = 0.1), could significantly reduce mean levels of serum creatinine. Nevertheless, AO could not reduce the incidence of mortality, with an OR of 0.94 (95% CI 0.69-1.28; p = 0.7). CONCLUSIONS: Overall, antioxidants such as NAC, vitamin C, and vitamin E can reduce the incidence of CIN, while only NAC might be able to significantly lower serum creatinine levels. There is no impact of AO supplementation on mortality.